Comparative Incorporation of PNA into DNA Nanostructures - Ronnie O. Pedersen; Jing Kong; Catalina Achim; Thomas H. LaBean (Molecules, 2015)
DNA has shown great promise as a building material for self-assembling nanoscale structures. To further develop the potential of this technology, more methods are needed for functionalizing DNA-based nanostructures to increase their chemical diversity. Peptide nucleic acid (PNA) holds great promise for realizing this goal, as it conveniently allows for inclusion of both amino acids and peptides in nucleic acid-based structures. In this work, we explored incorporation of a positively charged PNA within DNA nanostructures. We investigated the efficiency of annealing a lysine-containing PNA probe with complementary, single-stranded DNA sequences within nanostructures, as well as the efficiency of duplex invasion and its dependence on salt concentration. Our results show that PNA allows for toehold-free strand displacement and that incorporation yield depends critically on binding site geometry. These results provide guidance for the design of PNA binding sites on nucleic acid nanostructures with an eye towards optimizing fabrication yield.